Can the production of wild forest foods be sustained in timber concessions? Logging and the availability of edible caterpillars hosted by sapelli (Entandrophragma cylindricum) and tali (Erythrophleum suaveolens) trees in the Democratic Republic of Congo - Muvatsi, P.; Kahindo, J.M.; Snook, Laura K. (Elsevier, 2018)
Sapelli (Entandrophragma cylindricum) and tali (Erythrophleum suaveolens) are among the most important timber species harvested from Congo Basin forests. They also host edible caterpillars, Imbrasia oyemensis and Cirina forda, respectively, which are important to the nutrition and income of rural and urban populations. This study evaluated the density of these tree species within a 10 km radius around each of 4 villages and in the 2012 annual cutting areas of two timber concessions in the region of Kisangani (DRC). Sapelli and tali trees ≥20 cm dbh and their stumps were identiﬁed and measured on 21 ﬁve ha plots around each village and 20 ﬁve ha plots on each concession. Around villages and on concessions, sapelli trees occurred at densities of 0.048 ± 0.008 harvestable trees (≥80 cm dbh) ha −1 and 0.135 ± 0.019 precommercial trees ha −1. Harvestable tali trees (≥60 cm dbh) were seven times more abundant at 0.347 ± 0.032 ha −1, while pre- commercial tali trees occurred at densities of 0.329 ± 0.033 trees ha −1. Between 25% and 40% of the har- vestable sapelli trees had been logged as compared to < 3% of the harvestable tali trees. Production per tree, derived from another study, was extrapolated to estimate caterpillar yields on a half circle of 15,700 ha within 10 km of villages, using these estimates of tree densities. Depending on the village, yields were estimated as 11.6–34.5 Mg year −1 of I. oyemensis from sapelli trees, and 65.8–80.9 Mg year −1 of C. forda from tali trees, an average of 0.74–2.2 kg ha −1 year and 4.2–5.2 kg ha −1 year, fresh weight, respectively (0.23–0.68 kg ha −1 year −1 and 1.3–1.6 kg ha −1 year −1, dry weight, respectively). Harvestable trees yielded more caterpillars, providing most of the C. forda caterpillars. However, because harvestable sapelli trees oc- curred at low densities, the bulk of I. oyemensis caterpillar production would be hosted on precommercial trees. Logging practices that reject poorly formed or hollow trees and guidelines that call for high minimum diameter limits and retention of seed trees or prohibit logging on slopes or riparian zones, safeguard edible caterpillar production. Multiple resource management for multiple stakeholders would require more deliberate planning and management approaches based on negotiations with local communities and approaches like setting aside collection zones or collection trees that would be protected from logging.